2016
DOI: 10.18632/oncotarget.12809
|View full text |Cite
|
Sign up to set email alerts
|

Marital status is an independent prognostic factor for tracheal cancer patients: an analysis of the SEER database

Abstract: BackgroundAlthough marital status is an independent prognostic factor in many cancers, its prognostic impact on tracheal cancer has not yet been determined. The goal of this study was to examine the relationship between marital status and survival in patients with tracheal cancer.ResultsCompared with unmarried patients (42.67%), married patients (57.33%) had better 5-year OS (25.64% vs. 35.89%, p = 0.009) and 5-year TCSS (44.58% vs. 58.75%, p = 0.004). Results of multivariate analysis indicated that marital st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Association of marital status and the prognosis of cancer such as hepatocellular carcinoma, pancreatic neuroendocrine tumor and tracheal cancer was widely explored before 44 46 , which consistently suggested that marital status is an independent prognostic factor. Single patients have the higher risk of overall death compared with married group in our study, which is comparable with prior studies 31 , 44 46 . Potential mechanisms of phenomenon are unknown, we supposed that widowed patients lack care contribute to poor prognosis of MBC.…”
Section: Discussionmentioning
confidence: 99%
“…Association of marital status and the prognosis of cancer such as hepatocellular carcinoma, pancreatic neuroendocrine tumor and tracheal cancer was widely explored before 44 46 , which consistently suggested that marital status is an independent prognostic factor. Single patients have the higher risk of overall death compared with married group in our study, which is comparable with prior studies 31 , 44 46 . Potential mechanisms of phenomenon are unknown, we supposed that widowed patients lack care contribute to poor prognosis of MBC.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, plenty of studies have been performed to dig out the relation between biopsychosocial factors and diverse diseases, such as ischemic heart disease, diabetes mellitus and chronic pain [ 22 24 ]. Gradually, importance has been attached to the function of biopsychosocial factors in cancer patients [ 25 , 26 ]. A longitudinal study aiming at marital status and mortality in British women found that being single was associated with higher mortality instead of being divorced and being widowed [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among the studies, however, marital status, which plays an important role in women’s physical and mental health, has rarely been investigated for its effect on the EOC prognosis. In recent years, many researches have demonstrated that marital status independently predicts the survival of gastric cancer [ 6 8 ], colorectal cancer [ 9 , 10 ], liver cancer [ 11 ], pancreatic cancer [ 12 ], and several other types of cancer [ 13 16 ]. Identifying the relationship between the marital status and the survival of EOC would help researchers, doctors, as well as policy makers better cope with the increasing trend of mortality rate.…”
Section: Introductionmentioning
confidence: 99%